2014
DOI: 10.1007/s13277-014-2893-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide haplotype association study identifies BLM as a risk gene for prostate cancer in Chinese population

Abstract: Prostate cancer (PC) is a common malignant tumor that occurs in the prostate epithelial cells. It is generally considered to be caused by both genetic and environmental factors. To identify the genetic risk factors of PC in Chinese population, we carried out a genome-wide haplotype-based association study. The 33 Chinese PC cases were from the public GEO database (GSE18333), and the 139 Chinese controls (CHB) were from the HapMap project. Our analysis included three stages: (1) identifying the linkage disequil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…We first estimated the haplotypes and their frequencies in the LD blocks using the maximum likelihood (ML) method and expectation-maximization (EM) algorithm. Then, we performed the chi-square test for haplotype-phenotype association 26 , and statistical significance was also determined. We considered raw P -values ( P raw ) <1 × 10 −7 as significant and P -values <0.05 after 100,000 permutations as genome-wide significant (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…We first estimated the haplotypes and their frequencies in the LD blocks using the maximum likelihood (ML) method and expectation-maximization (EM) algorithm. Then, we performed the chi-square test for haplotype-phenotype association 26 , and statistical significance was also determined. We considered raw P -values ( P raw ) <1 × 10 −7 as significant and P -values <0.05 after 100,000 permutations as genome-wide significant (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have also shown that BLM is highly expressed in breast cancer tissue and represents a novel breast cancer biomarker [21, 22]. Nonsense mutations in the BLM gene increase the risk of PC [23], and BLM expression is associated with PC susceptibility in the Chinese population [24]. Previous work has shown that knockdown of BLM inhibits PC cell proliferation and promotes PC apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies did not find a positive association between this mutation and prostate cancer nor with ovarian cancer [Antczak et al, 2013;Bogdanova et al, 2015]. An increased risk for prostate cancer was found in Chinese men with a BLM haplotype block [Wang et al, 2015]. Mono-allelic loss-of-function BLM mutations were also found at a higher frequency than expected in an Australian highrisk breast cancer cohort [Thompson et al, 2012] and in an early-onset colorectal cancer cohort from the Netherlands [de Voer et al, 2015].…”
Section: Structure and Function Of The Blm Genementioning
confidence: 94%